How and when servant leadership enhances life satisfaction. Issue 5 (19th June 2018) - Li, Yanping; Li, Diwan; Tu, Yidong; Liu, Jie
Abstract : Purpose: The purpose of this paper is to investigate the relationship between servant leadership and life satisfaction through the mediating role of workplace positive affect (WPA), and the moderating roles of collectivistic orientation and general self-efficacy. Design/methodology/approach: Using a sample of 304 employees in a two-wave survey, the hypotheses were demonstrated with hierarchical regression analyses. Findings: The results revealed that servant leadership was positively related to employee life satisfaction, and WPA served as a mediator between them. Moreover, collectivistic orientation and general self-efficacy moderated the relationship between servant leadership and WPA, and the indirect effect of servant leadership on life satisfaction via WPA. Research limitations/implications: The time-lagged research design of this study may limit the ability to draw causal conclusions. Moreover, as this research was conducted in a Chinese context, the question of the generalizability of our findings calls for more attention. Practical implications: Leaders are encouraged to adopt the servant leadership style to facilitate employee life satisfaction and organizations should select and recruit managers with servant leadership qualities. Furthermore, because employees' collectivistic orientation and general self-efficacy moderate the effects of servant leadership on followers' outcomes, managers need to take individual differences into consideration when they implement managerial strategy. Originality/value: This research contributed to a burgeoning stream of servant leadership literature by investigating the functions of servant leadership in promoting life satisfaction, and exploring the affective mechanism linking servant leadership and life satisfaction as well as the boundary conditions of collectivistic orientation and general self-efficacy.